Recent Study on Strategic Planning of a Dental Clinic in India - Shalu Jain (New Frontiers in Medicine and Medical Research Vol. 4, 2021)
One is usually conflicted between pursuing a career in academia or starting their own practise after completing undergraduate or postgraduate degrees. Due to the fact that finding a job in the dental industry is extremely tough in today’s market, the best option left is to create one’s own business. Despite the fact that it appears to be a simple activity, it is not. It covers all of the necessary stages and obstacles to starting a successful dentistry practise in India. The majority of research on practise management is available in the literature, but there is relatively little published information on how to start and grow a dental practise. As a result, every new dentist should be knowledgeable of all the important details that must be followed strategically step by step while starting a dental practice.